1-[3-(4-Chlorophenyl)-5-(4-methoxyphenyl)-4,5-dihydro-1H-pyrazol-1-yl]butan-1-one - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the title compound, C(20)H(21)ClN(2)O(2), the benzene rings form dihedral angles of 6.35 (5) and 81.82 (5)° with the mean plane of the 4,5-dihydro-1H-pyrazole ring (r.m.s. deviation = 0.145 Å). This latter ring adopts an envelope conformation with the CH grouping as the flap. The dihedral angle between the benzene rings is 75.63 (4)°. In the crystal, molecules are linked by C—H⋯Cl and C—H⋯O hydrogen bonds into chains along [-201]. The crystal structure also features C—H⋯π interactions.